LEV NIKOLAYEVICH TOLSTOY - THE PEDAGOGY OF FREEDOM - Aura HAPENCIUC (Association of Social and Educational Innovation, 2021)
The paper highlights a different side of the concerns of the writer Lev Nikolayevich Tolstoy (1828-1910), his contribution at the level of pedagogy. One of the world's leading novelists, playwright and essayist, L.N. Tolstoy is also an important reformer of education, with a revolutionary pedagogical theoretical and practical work at the level of the '60s and '70s. The epistemological maturation of the Russian pedagogy occurs through the pedagogical activity and works of the authors K.D. Ushinsky and L.N Tolstoy. The two important Russian pedagogues, with universal impact, mark the moment of transition from the pre-modern pedagogy to the modern pedagogy. K. D. Ushinsky bequeathed the idea of the organic synthesis in pedagogy, and L.N. Tolstoy launched the pedagogical and social theme of freedom, in education and through education. In summary, the epistemological construction of the pedagogy of freedom can be demonstrated by the object of study, normativity and research methodology. The specific study object of L.N. Tolstoy's pedagogy is the free education / instruction as a model of formation through higher culture (Bildung), but it also involves other concepts that define: education (forced through instruction / teaching), general purpose, education contents and free school. The pedagogy of freedom anticipates the current New education (affirmed in Europe during the late nineteenth century - the second half of the twentieth century). The normativity specific to Tolstoy's pedagogy refers to the principle of complete freedom in education / instruction, the principle of organizing education / instruction in free schools, the principle of optimizing the relationship between the "two active factors of instruction: the educator and the educated". The historical and comparative research highlights the difference between education (constraining through training / teaching) and instruction (free education through higher culture - Bildung).